Television Writing : the ground rules of series, serials and sitcom. - Aronson, Linda (Allen & Unwin, 2005)
The restrictions governing the development and writing of TV drama series, serials and sitcom are a surprise to the newcomer and challenge to the veteran. This invaluable book describes the conventions, formats and everyday running of television writing. With contributions from a range of television drama experts, it explains the rules and provides practical advice on how to excel within them. An indispensable reference guide for anyone who is in television drama or sitcom, or wants to be.- Resumé vydavatel
Keywords: televizní scenáristika; tvůrčí psaní; television authorship; creative writing; elektronické knihy; příručky; electronic books; handbooks and manuals